Pharmacotherapy of Acute Bronchitis: Setting Priorities - A. A. Zaitsev; I. E. Budoragin; E. I. Isaeva; E. N. Vetrova; V. V. Tyusheva; N. A. Ivanova (Антибиотики и Химиотерапия, 2020)
The publication analyses the data on the etiology of acute bronchitis, the possibilities of determining the C-reactive protein in the disease, and the study of the clinical efficacy of the use of endogenous interferon inducers during the treatment of acute bronchitis. Acute bronchitis is a disease of predominantly viral etiology (influenza and parainfluenza viruses, adenoviruses, and combinations of various viruses). The presented results demonstrate the high practicability of acute bronchitis treatment with Kagocel® in comparison with the actual practice of pharmacotherapy.